Evaluation on the factors influencing the deposition of wax using full factorial design - Norida, Ridzuan; A. A., Azhar (Universiti Malaysia Pahang, 2019)
The purpose of this study is to determine the rate of wax deposition of Malaysian crude oil by evaluating the operational factors using full factorial design (FFD) approach (Design Expert version 7.1.6). Four factors were studied, which are rotation speed (A), cold finger temperature (B), experimental duration (C) and type of wax inhibitor (D), Poly(ethylene-co-vinyl acetate) (EVA) and xylene were used as a wax inhibitor. The individual effects of each factor and its interaction effects towards the response variable were studied. The result demonstrated that fewer wax deposit was obtained (0.0055 g) when optimal conditions of 2 h duration with 600 rpm rotation speed at 15°C cold finger temperature and EVA as an inhibitor were used. From the analysis of variance (ANOVA), factor B was found to be the main factor in affecting the wax deposit formation. However, the interaction between factors A and D shows the highest influence to reduce wax deposition. Furthermore, the model is designated with high determination coefficient (R2 = 0.8221), which explains 82.21% of the variability in the response. Hence, it can be concluded that factor B, and interaction between factors A and D need to be focused in controlling the parameters to minimize wax deposition.